Open‐label randomized non‐inferiority trial of a fixed‐dose combination of glimepiride and atorvastatin for the treatment of people whose Type 2 diabetes is uncontrolled on metformin. Issue 8 (12th December 2015) - Ambery, P.; Stylianou, A.; Atkinson, G.; Dott, C.; Baylor Curtis, L.; Haque, N.; LaCroix, K.; Min, K. W.; ,
Abstract: Aims: To evaluate, in a randomized, open‐label study, the non‐inferiority of a bioequivalent fixed‐dose combination of glimepiride and atorvastatin vs. separately co‐administered tablets in people with Type 2 diabetes mellitus. Methods: Participants with HbA1c ≥ 53 to < 80 mmol/mol (≥ 7.0 to < 9.5%), average fasting blood glucose > 7.0 mmol/l, who were on metformin for ≥ 3 months, were randomized to combination ( n = 215) or co‐administered glimepiride and atorvastatin ( n = 212) once daily for 20 weeks. Up‐titration of glimepiride (1–4 mg) and atorvastatin (10–20 mg) were based on average fasting blood glucose and LDL cholesterol, respectively. Co‐primary endpoints were change from baseline to week 20 in HbA1c and LDL cholesterol. Results: Non‐inferiority was demonstrated for both co‐primary endpoints: the upper limits of 95% CIs for differences (combination‐reference) were less than the prespecified margins of 3.3 mmol/mol (0.3%) for change from baseline in HbA1c [difference 0.1 mmol/mol (95% CI −1.6, 1.9); 0.01% (95% CI −0.15, 0.17)] and 6% for percentage change from baseline in LDL cholesterol [difference 0.87% (95% CI −2.47, 4.21)]. Similar proportions of participants on combination and reference had treatment‐emergent adverse events (64 vs. 61%). More participants on combination had hypoglycaemia (21 vs. 13%); most events were considered by the treating physician to be unrelated to study drug. Conclusions: The combination was non‐inferior to separately co‐administered tablets and the safety profile was consistent with the known profiles of glimepiride and atorvastatin. The observed increase in hypoglycaemia on the combination cannot be explained, but may be attributable to non‐systematic collectiof glucose readings and may have been influenced by reporting bias in this open‐label trial. What's new?: We evaluated a bioequivalent fixed‐dose combination of glimepiride plus atorvastatin versus separately co‐administered tablets in people with Type 2 diabetes mellitus on metformin. The combination was non‐inferior to separately co‐administered tablets with respect to reductions in HbA1c and LDL cholesterol after 20 weeks. The safety profile of the combination was consistent with the known profiles of glimepiride and atorvastatin. More participants on the combination reported hypoglycaemia. This cannot be explained but may be attributable to non‐systematic collection of glucose readings and may have been influenced by reporting bias in this open‐label trial.